Editorial - Lara, José Edson (Revista Gestão & Tecnologia, 2018)
One of the many terms that have been assumed and used in the scientific academia has been the "publisch or perish". Although it originates in the academic world of the United States, its approach has been intensifying in Brazil. The concept refers to and induces the compulsion for publications, usually intensive and uncreative, often on repetitive and at most incremental to the literary knowledge. Rare, therefore, are effectively innovative productions, in epistemic, conceptual, and morphological logics.